One coin – Scam cryptocurrency impact on Financial Market - Qadir, Aram Mohammed Amin; Ahmad, Rebwar Mohammed (Technium Social Sciences Journal, 2021)
In today we view a Scammers companies are evolving; however, Technology development and cryptocurrencies propagation, digital acceptance currencies by participants is a golden key in the hands of scammers companies, notwithstanding the companies Use a new cryptocurrencies name and new tags for it, many people and fans of Digital currencies fall with this scams network, with the reason for this scamming was they did against crypto buyer and seller, It caused a non-positive label for cryptocurrency.